2018
DOI: 10.1111/sltb.12523
|View full text |Cite
|
Sign up to set email alerts
|

How Distress Tolerance Mediates the Relationship Between Posttraumatic Stress Disorder and the Interpersonal Theory of Suicide Constructs in a U.S. Military Sample

Abstract: Objectives Despite the general suicide rate within the military being comparable to the general population when comparing peers, there are certain branches of the military that have elevated risk. Specifically, the U.S. National Guard has suicide rates that are constantly higher than other military branches and civilian peers. The National Guard are a unique military population in which they frequently transition between military and civilian life. With these unique experiences and heightened risk, military su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Stress tolerance moderated connections between profiles and anxiety, depression, and PTSD, similar to links found between stress tolerance and mental health in both civilian populations (Welle & Graf, 2011) and military populations (Martin et al, 2019). Specifically, stress tolerance had a mitigating effect for moderate structural (anxiety only), moderate emotional and elevated emotional (anxiety and depression), and high cumulative adversity (PTSD only) groups.…”
Section: Discussionsupporting
confidence: 60%
“…Stress tolerance moderated connections between profiles and anxiety, depression, and PTSD, similar to links found between stress tolerance and mental health in both civilian populations (Welle & Graf, 2011) and military populations (Martin et al, 2019). Specifically, stress tolerance had a mitigating effect for moderate structural (anxiety only), moderate emotional and elevated emotional (anxiety and depression), and high cumulative adversity (PTSD only) groups.…”
Section: Discussionsupporting
confidence: 60%
“…In terms of primary prevention, it may be helpful for researchers and clinicians to work toward the development and implementation of effective interventions designed to promote grit and other constructs of resiliency, such as distress tolerance, particularly for trauma‐exposed individuals. Distress tolerance, specifically, has been shown to exert an indirect effect on the relationship between PTSD and capability for suicide (Martin et al, ). It seems reasonable to extend the application of such research to other domains, such as the school system or other educational and social support services.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, low DT is associated with more severe PTSD symptoms in both veteran (Banducci et al, 2016) and civilian samples (Fetzner et al, 2014; Marshall-Berenz et al, 2011). Furthermore, among military personnel (Martin et al, 2018) and acute-care psychiatric inpatients (Vujanovic et al, 2017), DT mediated the relationship between PTSD and suicidality. Finally, longitudinal research has indicated that greater increases in DT during a residential treatment program lead to lower PTSD symptoms at discharge as compared to intake (Banducci et al, 2017).…”
mentioning
confidence: 99%